Color stability of acrylic teeth immersed in a pigmenting solution - Rojas Saldivar, Jessica Paola (2021)
Introduction: The use of partial and total prostheses are alternatives for integral treatment in oral rehabilitation that allow us to restore aesthetics, self-esteem and the ability to socialize among patients who use them. It is important that the acrylic resin artificial teeth used in these prostheses have beneficial properties such as color stability. Objective: To compare the color stability of acrylic teeth immersed in a pigmenting solution. Methods: An experimental in vitro study was carried out. The study was carried out on 40 acrylic teeth from two commercial companies immersed in coffee and distilled water (control), divided into 4 groups of 10 teeth each, G1 (Duratone-n® teeth immersed in distilled water), G2 (Duratone- n® immersed in coffee), G3 (Ivostar® teeth immersed in distilled water) and G4 for (Ivostar® teeth immersed in coffee). The specimens were immersed in their respective solution for 10 minutes a day for a period of 14 days. Finally the samples were stored in an incubator at a constant temperature of 37 ° C. The color was recorded in two times (initial time and at 14 days) using the Vita Easyshade® V spectrophotometer. Once the results were obtained, they were analyzed in the Stata 14 program. Results: Ivostar® teeth immersed in coffee (2.24) and water distilled (2.88) exhibited the highest ΔE values ​​compared to Duratone-n® teeth immersed in coffee (1.53) and distilled water (1.60). Conclusion: It was concluded that after exposure to coffee the teeth of the Duratone-n® brand presented greater color stability compared to the teeth of the Ivostar® brand.